Luca Chiantore, Áurea Domínguez Moreno y Silvia Martínez García: Escribir sobre música.: (Barcelona: Musikeon Books, 2016). ISBN 978-84-945117-0-7, 221 pp. (Revista Argentina de Musicología, 2016)
Reseña bibliográfica: Luca Chiantore, Áurea Domínguez Moreno y Silvia Martínez García: Escribir sobre música (Barcelona: Musikeon Books, 2016). ISBN 978-84-945117-0-7, 221 pp.